Silence! You do not arouse the innocent: sexuality, gender and education in understanding educators - Leivar Brancaleoni, Ana Paula [UNESP]; Oliveira, Rosemary Rodrigues de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
The school is a place permeated with sexuality. However, several studies Realize difficulties to deal with the subject in everyday school life. Sex education is also the subject of debates and controversies involving school staff, parents and researchers. This article aims to discuss the conceptions of sexuality and gender of teachers of a public school in Sao Paulo. In this research we used a qualitative approach. Data collection instruments were: participant observation and focus groups with educators. Data were systematically recorded in a field diary. and analyzed by the content analysis method. It was found that educators feel unprepared and did not wish to work with the theme. Attach to family responsibility of sex education. They understand that adolescence is the correct age to awaken sexuality. They understand that children are innocent because they are not interested in sex. It emphasizes the reduction of sexuality to sex and reproduction of heteronormative standards. Therefore, all students who do not meet the expected standards are seen as abnormal. The main cause attributed to the abnormality of these students is the family setting in which they are inserted.
Keywords: Sexuality; Gender; Sex education